Optical Properties of Al–Si–N Coatings Deposited by Reactive Magnetron Sputtering on Steel 12H18N10T and Zirconium Alloy E110; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 17, s. 1 - Konusov F. V. Fedor Valerievich; Pavlov S. K. Sergey Konstantinovich; Smolyanskiy (Smolyansky, Smolyanskii) E. A. Egor Aleksandrovich; Tarbokov V. A. Vladislav Aleksandrovich; Remnev (Remnyov) G. E. Gennady Efimovich; Kabyshev A. V. Alexander Vasilievich; Gadirov R. M. Ruslan Mukhamedzhanovich (2023, 2023)
Title screen